Decoding the rosetta stone of mitonuclear communication - English, Justin; Son, Jyung Mean; Cardamone, Maria Dafne; Lee, Changhan; Perissi, Valentina (Pharmacological Research, 2020)
Cellular homeostasis in eukaryotic cells requires synchronized coordination of multiple organelles. A key role in this stage is played by mitochondria, which have recently emerged as highly interconnected and multifunctional hubs that process and coordinate diverse cellular functions. Beyond producing ATP, mitochondria generate key metabolites and are central to apoptotic and metabolic signaling pathways. Because most mitochondrial proteins are encoded in the nuclear genome, the biogenesis of new mitochondria and the maintenance of mitochondrial functions and flexibility critically depend upon effective mitonuclear communication. This review addresses the complex network of signaling molecules and pathways allowing mitochondria-nuclear communication and coordinated regulation of their independent but interconnected genomes, and discusses the extent to which dynamic communication between the two organelles has evolved for mutual benefit and for the overall maintenance of cellular and organismal fitness.
Keywords: Animals; Cell Communication; Cell Nucleus; Gene Expression Regulation; Humans; Mitochondria; Mitochondrial Proteins; Nuclear Proteins; Signal Transduction; Acetyl-Coenzyme A (PubChem CID: 6302); Alpha-ketoglutarate (PubChem CID: 164533); Antimycin (PubChem CID: 12550); Carbonyl cyanide m-chlorophenylhydrazone (CCCP) (PubChem CID: 2603); Communication; Epigenetics; Humanin (PubChem CID: 16131438); Integrated stress response; Mitochondrial retrograde signaling; Mitonuclear; Nicotinamide riboside (PubChem CID: 439924); Oligoymycin (PubChem CID: 78358496); S-adenosylmethionine (SAM) (PubChem CID: 34756); Superoxide anion (PubChem CID: 5359597)